(untitled) (Actualizaciones en Sida e Infectología, 2021)
A pandemic is a multivariate phenomenon, like much of reality. However, within that complexity, a pandemic fundamentally involves social behaviors. Although the agent that triggers infection is usually a virus, the logics of contagion are determined by what humans do (travel, contact, care, etc.). This means that the central dimension of understanding and confronting a pandemic (especially when there are no biological interventions, such as treatments or vaccines) is linked to social behaviors. These behaviors are determined by collective representations, whether conscious (affected by accepted and recognized information), less conscious (affected by emotional and affective reactions), or even ethical and moral (affected by other prioritized values such as life, comfort, property, health, psychic integrity, among others). The responses that a society manages to articulate in the face of a pandemic are usually based on these three dimensions, and this is also the case in relation to COVID-19. In this 21st century, the three dimensions are in a problematic situation. We live in an era of unusual epistemological and moral relativism that calls into question both any information obtained by science and the ethical paradigms that have guided different communities throughout history. Conspiracy theories, fake news and the increasing fading of the need for demonstration have put scientific advances on an equal footing with any marginal speculation, hindering the first level that affects collective representations: the cognitive dimension. On the other hand, the abrupt transformations in daily life that lead to necessary isolation measures and the disruption generated by the danger to which one’s own life or that of loved ones is exposed when faced with the emergence of a novel virus (or any other traumatic event) mobilize strategies of denial and projection which, having an impact on emotional dimensions, constitute major obstacles to implementing the necessary caring behaviors. Articulated with the cognitive dimensions, these logics of denial and projection can involve serious dangers, both for the effectiveness of health decisions and for the levels of violence they can generate, as attempts to transfer frustrations, anger and fears against specific fractions of the population, projecting hatred and behaviors associated with it. Finally, the growing weakening of social ties in countries with growing inequalities, which have condemned large sectors to exclusion and marginalization, has led to the profound difficulty of reaching a consensus on principles for safeguarding the community, based on the priority of life over comfort or property, or on the need to build collective responses to face misfortunes or catastrophes. The risk of biomedical approaches is that, by focusing on the biological element of the pandemic phenomenon (the characteristics of the virus, advances in treatments, vaccine research, the material resources of health systems), they end up neglecting, as has happened in many diseases, the dimension with the greatest impact: social behaviors and the representations that determine them. Health capacity always has a finite horizon (often determined by the human resource, which is not scalable). Since contagion occurs through social behaviors, it is necessary to investigate ways of influencing such behaviors, from harm reduction campaigns to tracing and isolation strategies, from advocacy and information policies to strategies aimed at disarming forms of denial and projection, from the reconstruction of the community fabric to the definition of measures to prioritize the lives of all over the interests of some. Max Weber, one of the fathers of sociology, argued in the first volume of Economy and Society that the core of discipline lay in "the grasping of the meaning connection of social action.” A pandemic results in the ways in which a society can construct the meaning of what it is experiencing and, from there, propose actions to confront it. Paradoxically, this process is not biological, it is not determined by the virus or its characteristics, and it is not solved by chemicals, surgical interventions or vaccines, but is at the heart of the study of social practices. We are not at war against an invisible virus because viruses do not have subjectivity or intentions. Viruses do not have a perception of themselves or the ability to plan actions (although we often anthropomorphize them and, in an animistic way, believe that they do). We humans are the ones who transmit this virus and we humans are the ones who can change our behavior in a direction of care. But, to do so, we must understand that pandemics are social phenomena and we must challenge the meaning and representations that we construct about them.